2007
DOI: 10.1107/s0021889807010345
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive interlamellar interaction induced by addition of colloidal particles

Abstract: The effects of colloidal particles confined between lamellar membrane slits on interlamellar interactions have been investigated by small-angle neutron scattering. On addition of colloidal particles to a lamellar phase composed of a non-ionic surfactant, the first lamellar peak becomes sharper and higher-order peaks appear. Thus the colloidal particles suppress undulation fluctuations of lamellar membranes by their steric hindrance, which results in a repulsive interlamellar interaction. As the interlamellar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Moreover, it has been demonstrated that nanoparticles can influence d-spacing in the lamellar phase, inducing bilayer attraction by suppressing layer undulations. [41][42][43][44][45][46] The power law of 2.2 at low-q for the L4Fh-40wt sample is a strong indication of this phenomenon.…”
Section: Structural Features At the Equilibriummentioning
confidence: 89%
“…Moreover, it has been demonstrated that nanoparticles can influence d-spacing in the lamellar phase, inducing bilayer attraction by suppressing layer undulations. [41][42][43][44][45][46] The power law of 2.2 at low-q for the L4Fh-40wt sample is a strong indication of this phenomenon.…”
Section: Structural Features At the Equilibriummentioning
confidence: 89%
“…The topology of these mesophases has been explained by both geometrical concepts, such as triply periodic minimal surfaces (TPMS) or the critical packing parameter, or more recently by statistical physics approaches. , Furthermore, it has been proved that the interactions which stabilize any of the two domains forming the mesophases, can be further tuned by adding colloidal nanoparticles partitioning in any of the domains. , It is well-known that particles self-assemble when they are dispersed in an ordered matrix due to the entropic contributions originating by the mixing of the matrix and the particles . The effect of guest components on the lyotropic lamellar phase has been investigated in detail by several groups. The finally self-assembled system results from a balancing mechanism between entropic and energetic interactions. By doping a nanostructured matrix with colloidal nanoparticles of comparable size, additional interactions arising from the geometrical restrictions imposed by the ordered material matrix may trigger structural changes in the hosting media itself.…”
Section: Introductionmentioning
confidence: 99%
“…This effective attractive inter-lamellar interaction (depletion interaction) destabilizes the lamellar membranes and finally causes a phase separation into a dilute lamellar phase where the polymer chains are localized in and a concentrated lamellar phase as shown by Ligoure et al [13][14][15] On the other hand, when one confines colloids between the lamellar membrane slits, the colloids suppress the fluctuation of lamellar membranes, which leads an effective repulsive interaction between membranes. [16][17][18][19][20] The suppression of membrane fluctuations causes a morphological transition from lamellar membranes to worm-like micelles to release the geometrical frustration. 20 The structural transitions induced by the guest particles might be more emphasized, when the guest particles are confined into a closed capsule.…”
Section: Introductionmentioning
confidence: 99%